Vegetation of European springs:High-rank syntaxa of the Montio-Cardaminetea - Mucina, Ladislav; Zechmeister, H. (1994)
A survey of high-rank syntaxa of vegetation of European springs (class Montio-Cardaminetea) is presented. It shows the complexity of the class and the relations betweenthe units. More than 1200 relevés were arranged into sixphytosociological tables, each representing an alliance. Asynoptic table comprising all alliances is presented. Bryophytesare the most important group in most of the communities,both regarding biomass and cover. The Adiantetea andthe Montio-Cardaminetea are combined into one class. As to floristics and ecology, there are no obvious reasons to distinguish more than one order in this class. The vegetation of European springs is divided into six alliances: (1) Adiantion,split into two new suballiances, Adiantenion and Lycopodo-Cratoneurenion; (2) Cratoneurion commutati; (3) Cardamino-Montion – incl. three new suballiances: Mniobryo-Epilobienionhornemannii, Swertio-Anisothecienion and Cardamino-Montenion; (4) Dermatocarpion; (5) Epilobio nutantis-Montion; (6) Caricion remotae – incl. two new suballiances:Caricenion remotae and Cratoneuro filicini-Calthenion laetae.The alliances are floristically and ecologically characterizedand their distributions in Europe shown on maps.